Genetic parameters estimation, correlations and selection indexes for six agronomic traits in soybean lines F8 - Leite, Wallace de Sousa; Pavan, Bruno Ettore; Matos Filho, Carlos Humberto Aires; Neto, Francisco de Alcantara; Oliveira, Cleidismar Barbosa de; Feitosa, Fabiano Soares (Comunicata Scientiae, 2016)
This study aimed to estimate genetic and phenotypic parameters and provide knowledge for breeding programs aiming at the selection of the main characters of assessment in soybeans. The experiment was installed in Sabia farm, located at ‘Serra das Laranjeiras” , in the municipality of Currais, Piaui, Brazil, during the 2011/2012 crop year using a randomized block design with 27 genotypes and three repetitions. The evaluated variables were: height at flowering (APF), height at maturity (APM), pod insertion height (AIV), grain yield (PG), number of nodes (NN) and number of pods (NV). The obtained heritability coefficients were from medium to high, for all evaluated characters, ranging from 0.53 to 0.94, for grain yield and plant height at flowering, respectively. These high heritability were confirmed by the high degree of genetic variation and the CVg/CVe ratio, indicating a high prospect of success for the phenotypic selection. The higher positive genetic correlations and the significant (P <0.01) were observed between grain yield and the variables number of nodes (0.807**) and number of pods (0.781**), indicating that the selection of plants with higher number of nodes and pods could result in more productive plants. The Williams-based index presented the highest percentage of gain with the selection offor the grain yield (21.84%) variable.